Perspectives Regarding the Risk of Introduction of the Japanese Encephalitis Virus (JEV) in the United States - Oliveira, Ana R. S.; Cohnstaedt, Lee W.; Noronha, Leela E.; Mitzel, Dana; McVey, D. Scott; Cernicchiaro, Natalia (Frontiers in Veterinary Science, 2020)
Japanese encephalitis (JE) is a zoonotic, emerging disease transmitted by mosquito vectors infected with the Japanese encephalitis virus (JEV). Its potential for emergence into susceptible regions is high, including in the United States (US), and is a reason of economic concern among the agricultural community, and to public health due to high morbidity and mortality rates in humans. While exploring the complexities of interactions involved with viral transmission, we proposed a new outlook on the role of vectors, hosts and the environment under changing conditions. For instance, the role of feral pigs may have been underappreciated in our previous work, given research keeps pointing to the importance of susceptible populations of wild swine in naïve regions as key elements for the introduction of emergent vector-borne diseases. High risk of JEV introduction has been associated with the transportation of infected mosquitoes via aircraft. Nonetheless, no JEV outbreaks have been reported in the US to date and results from a qualitative risk assessment considered the risk of establishment to be negligible under the current conditions (environmental, vector, pathogen and host). In this work, we discuss virus-vector-host interactions and ecological factors important for virus transmission and spread, review research on the risk of JEV introduction to the US considering the implications of risk dismissal as it relates to past experiences with similar arboviruses, and reflect on future directions, challenges and implications of a JEV incursion.